Developing a model of employment creation in border region: Gaharu cultivation and honey bee farming in Bengkayang, West Kalimantan, Indonesia - Nurul Bariyah (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Bariyah N. 2020. Developing a model of employment creation in border region: Gaharu cultivation and honey bee farming in Bengkayang, West Kalimantan, Indonesia. Biodiversitas 21: 5237-5247. The border regions possess political, cultural, and socio-economic complexity. One of major problems in the border regions is the lack of employment opportunity following ups and downs in the economy, suggesting a need for a more sustainable employment opportunity by harnessing local conditions and practices. The main objective of the research was to construct an economic development model in the border region by integrating available natural resources, local initiatives, and external support to provide employment opportunities. We conducted the research in Jagoi Village, Bengkayang District, West Kalimantan, Indonesia which has border with Sarawak, Malaysia. We collected primary data through in-depth interviews, structured interviews, observation, and focus group discussion combined with secondary data. This information was then used to construct the model. Our research found that the population of Jagoi Village consisted of farmers (50%), menial laborers (30%), traders (17%), civil servants (2%), and ojek taxi drivers (1%). In the past, they also received additional income from collecting wild bee honey and gaharu (agarwood) resin. However, large tracks of forest area were cut by commercial loggers or converted into oil palm plantations. Fortunately, Jagoi Village has adat forest which preserved the forest from the expansion of oil palm plantation and is a source of non-wood products to use by the community could use. The research revealed that collecting wild bee honey and gaharu was no longer viable. Started from these conditions, we proposed a model of employment creation by cultivating gaharu and farming honey bee. As such, there is paradigm change from ‘collecting’ or ‘gathering’ into ‘cultivation’ and farming. To be successful, the model integrates six elements, consisting of awareness building, local initiatives, success stories as an example, external support or empowerment, field school, and independent execution. Using this approach the target community will be able to create new employment opportunities which eventually increases their income and prosperity.